ENT 530 Social Media Portfolio: Abchocojar / Nasimah Mohd Zainudin - Mohd Zainudin, Nasimah (2021)
Abchocojar offers chocolate-filled items to please customers. It recognizes the people who want to make grain chocolate as their snacks. The cost of the commodity is affordable. This product is also intended to be purchased by infants, families and students. The marketing strategy of Abchocojar is to emphasize product quality and cost. I therefore establish a marketing strategy to buy abchohojar that gives attraction. The taste is tasty and the item is of high quality. Abchocojar's management consists of Nasimah binti mohd zainudin. I build Facebook through social media to extend my company and learn how to post Facebook post for business product, whether teaser post, soft sell or hard sell. I do not target any specific area because my customers can be from anywhere. Our services can actually be done and managed online, and we do not need a face-to-face service. I have to promote the product, particularly in Pahang, through social media in Malaysia. For me, it is a challenge to market this product as my own project.